Dynamic conductance characteristics in HfOx-based resistive random access memory. Issue 21 (24th February 2017) - Chen, Ying-Chen; Chang, Yao-Feng; Wu, Xiaohan; Zhou, Fei; Guo, Meiqi; Lin, Chih-Yang; Hsieh, Cheng-Chih; Fowler, Burt; Chang, Ting-Chang; Lee, Jack C.
Abstract : Schematic of RESET analysis by dynamic conductance of I – V curve in HfO x -based resistive switching memory. Abstract : Characteristics of HfO x -based resistive switching memory (RRAM) in Al/HfO x /Al and Al/AlO x /HfO x /Al structures were studied using a dynamic conductance method. Step-like RESET behaviors as well as pre- and post-RESET regions of operation were characterized. The results indicated that defects at the oxide interface caused cycling issues in the Al/AlO x /HfO x /Al structure. No such RESET behavior was observed for the Al/HfO x /Al structure. Current induced over-heating, which caused an early RESET event, could be avoided using current-sweep technique that caused less electrical and thermal stress in localized regions. The experimental results not only provided insights into potential reliability issues and power management in HfO x -based RRAM, but also helped clarifying the resistive switching mechanisms.